Extractive use, management and in situ domestication of a weedy palm, Astrocaryum tucuma, in the central Amazon - Schroth, Götz; Mota, M.S.S. da; Lopes, R.; Freitas, A.F. de (2004)
Of particular interest for extractivism in tropical forest areas are useful species that occur at high density, such as the palm tucuma (Astrocaryum tucuma Martius-syn. A. aculeatum G.F.W. Meyer), a colonizer of disturbed areas in the central Amazon, whose edible fruits have found an interesting market in that region. However, with an expected increase of tucuma plantations, the future of tucuma extractivism will depend on its capacity to produce fruits not only of sufficient quantity but also of consistently high quality. We studied the productivity and fruit quality of an extractively used population of tucuma palms in an area of 9 ha within a 25 ha shifting cultivation landscape composed of crop fields, homegardens, fallows and secondary forests in the proximity of Manaus during a 24-month period. The average density of tucuma palms was 30.4 ha-1, with highest values in secondary forests (43 ha-1) and lowest values in homegardens (19 ha-1). In contrast, the percentage of productive palms was higher in fields (93%) and homegardens (88%) than in fallows (66%) and secondary forests (50%), apparently as a combined effect of previous management and delayed reproduction under shade. Fruit yield per productive palm was significantly higher in homegardens (47 kg) than in fallows (16 kg) and secondary forests (15 kg), with intermediate values in the fields (27 kg). The most productive palms produced fruits of intermediate quality as measured through a taste index, while few palms producing high-quality fruits were also high yielding. A management plan was developed that allows maximization of fruit yields while progressively improving the quality characteristics of the extractively used population in an in situ domestication process. Being a low-cost and low-risk strategy, "improved extractivism" can be an appropriate way of growing the arboreal weed, tucuma, and can contribute to increased farm income while increasing the economic value of disturbed areas in the central Amazon